Fragility Curves for Seismic Vulnerability of Back-to-Back Mechanically Stabilized Earth Walls - Rahimi, Maryam; Firoozfar, Alireza; Alielahi, Hamid (Geotechnical and geological engineering, 2024)
Back-to-back mechanically stabilized earth walls (BBMSEWs) are a specialized type of reinforced soil structure widely employed in the stabilization of embankments, roads, and bridge abutments. Despite their prevalent use, the technical understanding of these structures, particularly their seismic performance, remains limited. Given the inherent randomness of earthquakes, the seismic response of structures is often evaluated probabilistically, with fragility curves serving as a popular tool for assessing the likelihood of varying degrees of damage or failure. In this study, a specific BBMSEW configuration is simulated and validated using FLAC2D software. Following this, nonlinear dynamic analyses are performed to develop both scalar and vector fragility curves, based on peak ground acceleration (PGA) and peak ground velocity (PGV), under far-field and near-field seismic conditions. The study further investigates the influence of metal strip overlap length on the vulnerability of these walls. The results not only facilitate the prediction of wall vulnerability across different seismic intensities but also reveal that increasing the overlap length of the metal strips from 0.65 to 0.85 times the wall height can reduce the probability of seismic damage by up to 35% in far-field earthquakes and up to 50% in near-field earthquakes. Moreover, the study finds that vector fragility curves provide a more realistic assessment compared to scalar fragility curves.